THE ROLE OF SELF-EFFICACY AND INTRINSIC MOTIVATION IN PREDICTON OF HEALTHY LIFESTYLE INTENTIONS - Hakobjanyan, A.R. (Modern Psychology, 2025)
The current article reviews the results of a study of social-cognitive and motivational predictors of health behaviour. The theory of planned behavior was tested by using a TPB questionnaire and Treatment Self-Regulation Questionnaire was used. In the result of the step-wise multiple regression, self-efficacy and autonomous motivation were revealed as main predictors for healthy eating, physical activity and smoking cessation. Thus, healthy lifestyle can be constructed by self-regulation process.